Hypomelanosis of Ito: case report - Osmel Mollinedo-Rangel (Universidad Médica Pinareña, 2020)
Introduction: hypomelanosis of Ito is a neurocutaneous syndrome and a multisystem disorder, described by Japanese dermatologist Minor Ito in 1951. This disease is characterized by hypopigmented lesions of linear or annular distribution on the skin, associated or not with neurological and ocular manifestations, as well as dental and musculoskeletal malformations.